Learning motivations and effort beliefs in Confucian cultural context: A dual-mode theoretical framework of achievement goal - Chen, Shun-Wen (Frontiers in Psychology, 2023)
For decades, results of international academic assessments have shown that students in the Confucian cultural circle performed outstandingly well. However, many studies have shown that mainstream Western motivation theories could not comprehend the learning motivation and performance of East Asian learners. Therefore, from the perspective of cultural psychology, the author proposed a dual-mode theoretical framework and differentiated two types of achievement goal that an individual may pursue in daily life. The personal goals are based on autonomous interest, with little reference to social expectations or values, whereas the vertical goals are related to social role obligations, the contents and standards of which are of little relevance to personal choice. A series of empirical studies showed that for Taiwanese students, parents and teachers, pursuing academic achievements was an important vertical goal with highly social expectations. Students who met such expectations were deemed good students and likely to be viewed as possessing high learning virtues. Moreover, on the basis of the framework, people may develop two kinds of effort beliefs when pursuing academic achievements. The obligation-oriented belief about effort is to believe that making effort in learning is a student’s role obligation. The improvement-oriented belief about effort is to believe that effort can conquer one’s limitations and improve one’s academic performance. Results of empirical studies showed that these effort beliefs could predict student’s learning emotions, cognitions and behaviors. Furthermore, students’ effort beliefs could be influenced by their parents’ and teachers’ effort beliefs. The cultural and practical implications of the framework are discussed.